Alcohol Oxidation: Air‐Assisted Transient Synthesis of Metastable Nickel Oxide Boosting Alkaline Fuel Oxidation Reaction (Adv. Energy Mater. 46/2020). Issue 46 (8th December 2020) - Liu, Chang; Zhou, Wei; Zhang, Jinfeng; Chen, Zelin; Liu, Siliang; Zhang, Yang; Yang, Jiaxing; Xu, Lianyong; Hu, Wenbin; Chen, Yanan; Deng, Yida
Abstract : In article number 2001397, Yanan Chen, Yida Deng, and co‐workers report the fabrication of metastable NiO nanoparticles on carbon cloth (NiO@C/CC) via an air‐assisted thermal shock technique (ATS‐tech) as an efficient alcohol oxidation reaction catalyst. This rapidly synthesized NiO@C/CC has superior catalytic activity and stability, which provides a reference for the design and manufacture of high‐performance non‐noble metal catalysts for alcohol oxidation reactions.